Talking Stick Versus Direct Instruction Method and Learning Style of Critical Thinking Skills - Indah Dwi Jayanti; Ibut Priono Leksono; Atiqoh (Institute of Computer Science (IOCS), 2022)
This study aimed to determine the popularity of tourist destinations in Lombok Timur with three investigated categories; the destination for islands, nature, and beaches. We use descriptive statistical approaches with univariate and bivariate methods. A random survey using google forms was distributed to 196 respondents within a particular time. Some The aims of this study were to determine (1) to examine the differences between the Talking Stick Versus Direct Instruction method on critical thinking skills, (2) to examine the differences in learning styles to critical thinking skills, and (3) to examine the effect of the interaction between the Talking Stick Versus Direct method. Instruction and learning styles on critical thinking skills in Indonesian subjects. This quantitative research uses experimental methods. The researcher used SPSS 26 to calculate the two-way analysis of variance. The research design used is a 2x3 factorial design. Because this research was conducted in four classes, namely 2 experimental classes and 2 control classes. The experimental class was treated with the Talking Stick method while the control class was given the Direct Instruction learning method. In each control class and experimental class, they were divided into three groups, namely the audio, visual and kinesthetic groups. The data analysis technique in this study is a two-way analysis of variance with a significance level of = 5%. Based on the results of the data analysis, they are: (1) There are differences in the Talking Stick Versus Direct Instruction method on Critical Thinking Skills, (2) There are differences in learning styles on critical thinking skills, (3) There is an interaction effect between the Talking Stick Versus Direct Instruction method and the learning style. learn critical thinking skills. Based on the results of the study, it was concluded that using the Talking Stick Method and Learning Styles could improve Critical Thinking Skills. The implication of this research is that the Talking Stick Method can be used as a way to improve students' critical thinking skills.